Students’ Speaking Experience toward the Use of Role Play Technique in Online-Mediated Learning - Mutiara Wulandewi; Kusrin Kusrin; Putri Kamalia Hakim (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2021)
The researcher aimed to find out students’ speaking experience toward role-play techniques in online learning. The researcher used a descriptive case study to describe and interpret students' attitudes toward speaking online learning. The data collections were interview through Whatsapp and questionnaires on Google form. The researcher observed 5 students for the Interview and 34 eleventh grade students for the Questionnaire. The results showed that the participant's experience toward the implementation of role-play technique in online speaking class was good and positive. The most of participants claimed that they had an interesting experience. However, this research still had several obstacles such as limited internet access, lack of participants' language skills, and limited feedback from the researcher.